The relationship between eating habits and stress among undergraduate medical students of IIUM Kuantan - Pasi, Hafizah; Mohd Rus, Razman; Abd. Aziz, Karimah Hanim; Yusof, Muhammad Zubir; Nasreen, Hashima E; Ab Rahman, Jamalludin (Malaysian Public Health Physicians' Association, 2018)
Eating habits among medical students are associated with stress of university life and unhealthy eating habit among young adults is a public health concern in Malaysia. This study is conducted to determine the eating habit and its relationship with stress among undergraduate medical students of IIUM Kuantan. A cross sectional study was carried out among 250 undergraduate medical students using quota sampling. Self-administered online questionnaire consist of DASS-21 and Healthy Eating Assessment (Cronbach Alpha = 0.523) was distributed to Year 1 until Year 5. Data was analysed using SPSS software Version 23.0 and p value of <0.05 is taken as significant. 250 respondents consisting of 54.1% female with mean age of 22.89 (SD=1.571) and 95.6% of them unmarried were enrolled in this study. Majority have parents who attained university education and above (61.8% of father and 55% of mother). Mean Body Mass Index is 22.58 (SD=3.98), 24.7% practice regular exercise while only 5 respondents are current smoker. It is noted that there is a significant relationship between eating habits and stress level (p=0.004) with highest percentage of unhealthy eating habits among severe to extremely severe group (64.3%). There is no significant relationship between eating habits with other factors. Even though majority of the medical students in this study have healthy eating habits, result shows it is significantly related to stress. Therefore, students should manage their stress wisely to maintain healthy eating habits.